Epitope Addition and Ablation via Manipulation of a Dengue Virus Serotype 1 Infectious Clone - Emily N. Gallichotte (American Society for Microbiology, 2017)
ABSTRACT Despite the clinical relevance, dengue virus (DENV) research has been hampered by the absence of robust reverse genetic systems to manipulate the viral serotypes for propagation and generation of mutant viruses. In this article, we describe application of an infectious clone system for DENV serotype 1 (DENV1). Similar to previous clones in both flaviviruses and coronaviruses, the approach constructs a panel of contiguous cDNAs that span the DENV genome and can be systematically and directionally assembled to produce viable, full-length viruses. Comparison of the virus derived from the infectious clone with the original viral isolate reveals identical sequence, comparable endpoint titers, and similar focus staining. Both focus-forming assays and percent infection by flow cytometry revealed overlapping replication levels in two different cell types. Moreover, serotype-specific monoclonal antibodies (MAbs) bound similarly to infectious clone and the natural isolate. Using the clone, we were able to insert a DENV4 type-specific epitope recognized by primate MAb 5H2 into envelope (E) protein domain I (EDI) of DENV1 and recover a viable chimeric recombinant virus. The recombinant DENV1 virus was recognized and neutralized by the DENV4 type-specific 5H2 MAb. The introduction of the 5H2 epitope ablated two epitopes on DENV1 EDI recognized by human MAbs (1F4 and 14C10) that strongly neutralize DENV1. Together, the work demonstrates the utility of the infectious clone and provides a resource to rapidly manipulate the DENV1 serotype for generation of recombinant and mutant viruses. IMPORTANCE Dengue viruses (DENVs) are significant mosquito-transmitted pathogens that cause widespread infection and can lead to severe infection and complications. Here we further characterize a novel and robust DENV serotype 1 (DENV1) infectious clone system that can be used to support basic and applied research. We demonstrate how the system can be used to probe the antigenic relationships between strains by creating viable recombinant viruses that display or lack major antibody epitopes. The DENV1 clone system and recombinant viruses can be used to analyze existing vaccine immune responses and inform second-generation bivalent vaccine designs.